Glass : looking in, looking out - Theule, Larissa (Candlewick Press, 2026)
Meteoric collisions, volcanic eruptions, lightning strikes. Three catastrophes, all capable of producing glass: the stuff we use to protect us from the elements, send images, store energy, help with everyday tasks, and make medical and scientific progress possible. With the help of human ingenuity, glass has evolved from its lumpy natural origins to a refined wonder that helps humankind see into the farthest reaches of outer space and the smallest particles of life on earth. Glass is all around us and is one of the most versatile -- and sparkling -- marvels of the material world, still changing the way we build, the way we think, the way we see!